7x-2(5-x)=3+2x+1

Simple and best practice solution for 7x-2(5-x)=3+2x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-2(5-x)=3+2x+1 equation:


Simplifying
7x + -2(5 + -1x) = 3 + 2x + 1
7x + (5 * -2 + -1x * -2) = 3 + 2x + 1
7x + (-10 + 2x) = 3 + 2x + 1

Reorder the terms:
-10 + 7x + 2x = 3 + 2x + 1

Combine like terms: 7x + 2x = 9x
-10 + 9x = 3 + 2x + 1

Reorder the terms:
-10 + 9x = 3 + 1 + 2x

Combine like terms: 3 + 1 = 4
-10 + 9x = 4 + 2x

Solving
-10 + 9x = 4 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-10 + 9x + -2x = 4 + 2x + -2x

Combine like terms: 9x + -2x = 7x
-10 + 7x = 4 + 2x + -2x

Combine like terms: 2x + -2x = 0
-10 + 7x = 4 + 0
-10 + 7x = 4

Add '10' to each side of the equation.
-10 + 10 + 7x = 4 + 10

Combine like terms: -10 + 10 = 0
0 + 7x = 4 + 10
7x = 4 + 10

Combine like terms: 4 + 10 = 14
7x = 14

Divide each side by '7'.
x = 2

Simplifying
x = 2

See similar equations:

| 5*12+13+3*14+2*15+4*16+17+19+3*20/20 | | 12-8m=2m+2 | | 14-(2q+5)=(-2q)+9 | | -3/4x+5/4=x+3 | | 12x+4/4(x-1)(x+1)=5/4 | | 8x-16=4(2x-4) | | 22=4+3t | | x+30=93 | | -1/4y+5/4=-5/6y+5/3 | | -42=14y | | .2x-3=1 | | -5(9r+10)+5r=10(r+10) | | 2.2x-3=1 | | 3r^2+10r-4=84 | | 9-3(9z+1)=-4(-z-6)-8 | | x^3-19x=-30 | | 15=5/9(f-32) | | -2y+20=-5y+5 | | 300-20x=150+20x | | 3.7+3.25x= | | 11x-31=90 | | 21-1/24(3x)=14-1/24(2x) | | 4x6/11 | | 8x+42=90 | | -n+8.5=14.4 | | -2+8(n-3)=2(-9n-5)+7 | | 2x^2-38x=0 | | 2x+5=10y | | 3u-14=-6u-5 | | (3h-1)(h+5)= | | 25x^2+10x-24=0 | | -2.3(m-1.1)-4.6=-13.57 |

Equations solver categories